Perlindungan Hukum Terhadap Anak yang Melakukan Self-Harm “Nge Barcode” Berdasarkan Undang-Undang Nomor 35 Tahun 2014 (Studi Kasus Pusat Kajian Perlindungan Anak Kota Medan) - Yana Sebha Pasaribu (Jurnal Hukum Lex Generalis, 2025)
Self-harm "Nge Barcode" is an act of intentionally hurting oneself without the intention of ending one's life. This research aims to understand the legal protection for children as victims who engage in self-harm "Nge Barcode" based on Law Number 35 of 2014 on Child Protection in Medan City, to determine the role of the Child Protection Study Center (PKPA) in providing protection for children who engage in self-harm "Nge Barcode" in Medan City, and to identify the obstacles and challenges faced by the Child Protection Study Center (PKPA) in providing protection for children who engage in self-harm "Nge Barcode". This research employs a qualitative descriptive method with an empirical legal research type, initially examining secondary data, then continuing with field research for primary data.